Relationship between Serum Indoxyl Sulfate and Klotho Protein and Vascular Calcification in Patients with Chronic Kidney Disease Stages 3–5 - Yan Gao; Cong-Juan Zhao; Qiang Liu; Chen-chen Li; Zhe Li; Jing Li; Qian Wang; Li Zhang (International Journal of Endocrinology)
Objective. This study aims to explore the relationships between serum indoxyl sulfate (IS) and Klotho protein levels with vascular calcification in patients with chronic kidney disease (CKD) stages 3–5. Methods. From December 2021 to January 2023, a total of 108 CKD patients in stages 3–5 were enrolled in this cross-sectional investigation. Demographic information and routine clinical biochemistry test results were gathered. Serum levels of IS and Klotho were quantified through enzyme-linked immunosorbent assays. Furthermore, multislice spiral computed tomography was employed to evaluate vascular calcification. The association between serum IS or Klotho levels and abdominal aorta calcification was assessed using univariate analysis and logistic regression analyses. Results. With the progression of CKD stages, serum creatinine, phosphorus, intact parathyroid hormone (iPTH), serum IS, and abdominal aortic calcification exhibited incremental trends, while serum calcium and Klotho protein levels showed a diminishing trend, with statistically significant differences (P<0.05). Significant differences were observed in age, blood phosphorus, calcium, total parathyroid hormone, serum IS, and Klotho protein levels between patients with and without aortic calcification (P<0.05). Logistic regression analysis demonstrated that advanced age, high IS level, and low Klotho protein level were independent risk factors for abdominal aortic calcification in CKD patients (P<0.05). Conclusion. This study indicates elevated serum IS levels and decreased Klotho protein levels in CKD patients. High IS level and low Klotho level were independent risk factors for abdominal aortic calcification.